PENGARUH PERTUMBUHAN EKONOMI, PENDIDIKAN, DESENTRALISASI FISKAL, DAN BELANJA MODAL TERHADAP KETIMPANGAN PENDAPATAN - Putri, Nabila Dewi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
Despite the major economic contribution of Java, some economic problems persist; one of which is income inequality in five regencies and cities in the Special Region of Yogyakarta. The objective of this research is to examine the effects of economic growth, education, degree of fiscal decentralization, and capital expenditures on income inequality in the Special Region of Yogyakarta during the 2011-2021 period. The results of the analysis using panel data regression with Common Effect Model indicate that education and degree of fiscal decentralization significantly affect income inequality in the Special Region of Yogyakarta during the 2011-2021 period, while economic growth and capital expenditures have no significant impact on the income inequality in the said region during the aforementioned period.